Effects of ZrN and DLC coatings on morphostructural, corrosion, cell viability, and antibacterial properties of Ti6Al4V scaffolds - Aslan, Naim; Aksakal, Bunyamin; Cihangir, Salih; Fidan, Ferzan; Yilmazer, Yasemin (Springer Heidelberg, 2025)
Lightweight and functional metallic materials are consistently favored and attract significant attention in the biomedical field. This study investigates the influence of ZrN and DLC coatings on Ti6Al4V scaffolds with varying porosities (40%, 50%, 60%) for biomedical applications. PVD-deposited coatings exhibited distinct growth mechanisms: High-resolution SEM-FIB analyses revealed columnar ZrN structures due to limited adatom mobility, while DLC formed conformal, amorphous layers via high-energy carbon species. Corrosion resistance decreased in 40% porous DLC and 60% porous ZrN-coated samples, likely due to coating defects and increased electrolyte access through open pores. ZrN coatings showed superior antibacterial activity and attributed to surface reactivity and potential ion release. In contrast, the uncoated 60% porous scaffolds demonstrated highest cell viability, suggesting that excessive coating on highly porous structures may hinder cell-material interactions. Furthermore, the cytotoxicity evaluations indicated that uncoated scaffolds exhibited the highest cell viability (77.51%) at 60% porosity after 48 hours, with ZrN coatings demonstrating better efficacy compared to DLC in the 50% and 60% porosity groups.
Keywords: Biomaterial & biomedical; PVD coating; Corrosion; Microstructure; Porosity